Elements of effective anatomy teaching from the perspective of medical students - Saiful Bahri, Talip; Muhamad Saiful Bahri, Yusoff; Zul Izhar, Mohd Ismail; Siti Nurma Hanim, Hadie (Biome Scientia Sdn Bhd, 2022)
Previous research shows that effective anatomy teaching depends on several factors including the teaching approaches and lecturers' behaviour. However, evidence is scarce on effective teaching in anatomical sciences education. Therefore, this study aims to identify the elements of effective anatomy teaching from the perspective of medical students. A qualitative study was conducted by using a focus group discussion involving 52 medical students from one public medical school in Malaysia. The interview data were transcribed, converted into electronic format, and analysed using thematic analysis via the ATLAS.ti software. The analysis produced three themes, namely: (1) lecturer’s attributes and behaviour; (2) teaching approaches and strategies; and (3) teaching support. Each theme overlies several sub-themes that reflect a considerable number of effective teaching elements. In general, there are thirteen effective teaching elements generated, namely, (1) experience teacher; (2) self-confidence; (3) passionate teaching (4) teaching effort; (5) teachers’ character; (6) integrating different approach; (7) group activity task; (8) good lecturing strategies and techniques; (9) teaching and learning through visual modalities; (10) intraclass activity; (11) teaching tools and facilities; and (12) supplementary teaching session; and (13) online related learning. The findings of this study serve as a foundation for producing effective teaching guidelines that can enhance anatomy teaching in the future.